2020
DOI: 10.1002/emp2.12055
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department implementation of abbreviated magnetic resonance imaging for pediatric traumatic brain injury

Abstract: Pediatric head injury is a common presenting complaint in the emergency department (ED), often requiring neuroimaging or ED observation for diagnosis. However, the traditional diagnostic neuroimaging modality, head computed tomography (CT), is associated with radiation exposure while prolonged ED observation impacts patient flow and resource utilization. Recent scientific literature supports abbreviated, or focused and shorter, brain magnetic resonance imaging (MRI) as a feasible and accurate diagnostic altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Cohen et al stated “Rapid protocols for head MRI after acute brain injury in pediatric patients have been shown to reduce examination times while maintaining a high level of accuracy. They require only 3–6 min inside the scanner and ultimately a minimal level of sedation in agitated children” [ 42 , 43 ]. Using MRI for diagnostics in children therefore seems to be increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al stated “Rapid protocols for head MRI after acute brain injury in pediatric patients have been shown to reduce examination times while maintaining a high level of accuracy. They require only 3–6 min inside the scanner and ultimately a minimal level of sedation in agitated children” [ 42 , 43 ]. Using MRI for diagnostics in children therefore seems to be increasing.…”
Section: Discussionmentioning
confidence: 99%
“…However, rapid MRI protocols have been developed to evaluate children with possible ventriculoperitoneal shunt malfunction, and these protocols are now being applied to children with traumatic brain injury. 12,13 Although evidence is currently limited on the use of rapid MRI protocols for both the initial evaluation of children with traumatic brain injury and for monitoring for hemorrhage progression in children with intracranial hemorrhage, [13][14][15][16] it is clear that many institutions are adopting MRI. Between 2010 and 2019, we found that the rates of repeat CT scans decreased by 9% and subsequent MRIs increased by 8%, whereas overall rates of repeat neuroimaging remained stable.…”
Section: Discussionmentioning
confidence: 99%